Achievement of value for money in local government authorities: A case of Kahama town council - Kime, Semen Kukula (Mzumbe University, 2024)
A dissertation submitted to the school of business as partial fulfillment for the award of Master of Science in Procurement and supply Chain Management Degree (MSc-PSCM) of Mzumbe University.